(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3Gdbhd ai JChjd bhdg Ld KfGDg (B" (3Ef Gddg dGjXde eKbGd PQI hEf Jc MSfI jVGYagG hjDJg ef dOfg CLQkG YXjekG (B" (3bGd CHh LYaQ QMeg Gddg jYfi HPdc Ld KfGDg heGPG Ydjge dh GefhG HGddg s
(3BNQgG (B:s
(3jfJgi HJaSjQ GdBjI GdcQjeI (B" (3hdG JgfhG ai EHJZGA Gdbhe hjQLhf ef Gddg eGdG JQLhf (B" (3abGd (B: (3CHh SajGf ehYOfG hehYOge HOQ GdUZQi hajgG CfRdJ Ef jeSce bQY abO eQg Gdbhe bQY eKdg s
(3CKfGA JaSjQ ShQI GdfSGAs
(3cJHJ gPg GdfSNI Ydi Qb ZRGd ef JMHjS GdSdWGf CHj YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(37 / 80) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs